2018
DOI: 10.18051/univmed.2018.v37.3-12
|View full text |Cite
|
Sign up to set email alerts
|

Green tea moisturizer improves skin hydration in elderly

Abstract: BACKGROUND Dry skin is a major skin health problem in elderly. Green tea, which has an antioxidant effect, has recently been used as an active ingredient in moisturizing creams; yet the effect has not been well studied. This study compares the skin hydration effect of green tea and vitamin E moisturizer among elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A number of studies have demonstrated that the catechins prevent the collagenase and tyrosinase activity, resulting in the improvement of skin health [ 26 , 27 ]. In addition, it has been shown that green tea is effective for skin hydration in the elderly [ 28 ]. Here, green tea has dual functions including antioxidant and hydrating effects [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that the catechins prevent the collagenase and tyrosinase activity, resulting in the improvement of skin health [ 26 , 27 ]. In addition, it has been shown that green tea is effective for skin hydration in the elderly [ 28 ]. Here, green tea has dual functions including antioxidant and hydrating effects [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, moisturizing formulations may be helpful to hinder or overcome this issue. In a study conducted by Tjandra et al [ 28 ], it was reported that green tea-embedded moisturizing topical formulations have considerably more effect on skin hydration than those creams containing vitamin E.…”
Section: Resultsmentioning
confidence: 99%
“…
Moisturizers are the most common skin care products that are often used to reduce dry skin conditions by softening the skin, filling skin pores, and minimizing friction that is about the skin [1].Moisturizing preparations are used to prevent the evaporation of water on the skin and cause the skin to become moist and soft by forming a thin layer of fat on the surface of the skin. Everyone has different skin types.
…”
mentioning
confidence: 99%
“…Moisturizers are the most common skin care products that are often used to reduce dry skin conditions by softening the skin, filling skin pores, and minimizing friction that is about the skin [1].…”
mentioning
confidence: 99%